Redescription of Paccius quadridentatus Simon, 1898 (Araneae: Corinnidae: Trachelinae) based on the holotype - Marusik, Yuri M. (Zootaxa, 2009)
Paccius is a small genus of tracheline spiders with only eight species described from Madagascar (seven species) and Seychelles (one species) (Platnick, 2008). However, the genus is likely more diverse and may include as many as 25 species from Madagascar and adjacent islands such as Comoro, La Réunion, and Mauritius (Platnick, 2000). Only five species of this genus were properly illustrated and diagnosed by Platnick (2000). None of the three species described by Simon, including P. madagascariensis Simon, 1898, the type species, have ever been illustrated. The figures of P. quadridentatus in Benoit (1978) refer to Oedignatha mogamoga Marples, 1955 (Platnick, 2000). The only work with the first illustrations of Paccius species was published by Platnick (2000), who illustrated the copulatory organs of five species. The general habitus of Paccius has never been illustrated. While organizing the spider specimens remaining after the late Michael I. Saaristo, I found a vial with the holotype male of Paccius quadridentatus Simon, obviously borrowed from the Muséum National d’Histoire Naturelle, Paris. As I realized that this species was never thoroughly described, and the habitus of Paccius has never been depicted, I decided to provide a detailed redescription of P. quadridentatus, and provide figures of its habitus. Specimens were photographed using an Olympus SZX12 stereomicroscope and Olympus Camedia C-5050 camera. The images have been montaged using “CombineZM” image stacking software. The palp was macerated with lactic acid to make the passage of the seminal duct visible. All measurements are given in millimeters.